The Extent of Including 21st Century Skills in Omani Science Curricula for Grades (5-8) from Teachers' Point of View - Wafa Yaqoob Al-Housni; Mohamed Ali Ahmed Shahat (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
Objectives: This study aims to identify the extent to which twenty-first century skills are included in the Omani science curricula for grades (5-8) from teachers' point of view. Methods: A descriptive approach was used, and an online questionnaire was built. The study sample was randomly selected from teachers of the second cycle in the Sultanate of Oman. The size of the sample was (100) male and female teachers. Data were collected and analyzed using the Statistical Package for Social Sciences (SPSS). Results: The study concludes that the twenty-first century skills were moderately available in science curricula for grades (5-8) from the teachers' point of view. There was a statistically significant difference in the opinions of male and female teachers about the inclusion of twenty-first century skills in science curricula due to the gender. A statistically significant difference was also found in the direction of the differences in favor of females. The one-way analysis of variance also showed differences in opinions due to teaching experience in favor of those with little teaching experience. Conclusions: The study recommends including twenty-first century skills within the objectives of science education. In addition, it is important to represent more of society's needs and the requirements of the labor market in the science curricula and build enrichment activities to develop information technology skills and means of communication among students.